An experimental investigation of diesel soot thermal-induced oxidation based on the chemical structure evolution. (March 2022) - Guo, Yi; Horchler, Eva J.; Fairley, Neal; Stevanovic, Svetlana; Shang, Jing; Ristovski, Zoran
Abstract: Diesel particle emissions are a major environmental concern and understanding its oxidation mechanisms is essential for development of diesel particulate filters (DPF) regeneration strategy and the control of the secondary particle emissions produced during regeneration. This study used X-ray Photoemission Spectroscopy to examine the oxygen functional groups on the soot flake in sixteen partially oxidised soot samples generated under temperatures between 25 °C and 580 °C. We found that soot flake oxygen-containing functional groups evolution leads the oxidation. This study also compared the carbon skeleton of the secondary generated particles and original soot by using Raman spectroscopy, finding that the cleavage of the chemical bonds on the bridging sites contributes to the soot fragmentation thereby the secondary particle formation. It is concluded that oxygen-containing functional groups on the soot flake edge dominate the oxidation process thereby it is suggested as a major factor to consider for the DPF regeneration strategy development and secondary particle emission control. Graphical abstract: Image 1